Point spectrum of the schrödinger operator with point interactions at the vertices of regular N-gons - Dudkin, M. Ye. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We present a complete description of the point spectrum of the Laplace operator perturbed by point potentials concentrated at the vertices of regular polygons. We prove a criterion for the absence of points of the point spectrum of a singular perturbed positive self-adjoint operator with the property of cyclicity of defect vectors.